2007
DOI: 10.1073/pnas.0607450104
|View full text |Cite|
|
Sign up to set email alerts
|

Activity-dependent neurotransmitter-receptor matching at the neuromuscular junction

Abstract: Signaling in the nervous system requires matching of neurotransmitter receptors with cognate neurotransmitters at synapses. The vertebrate neuromuscular junction is the best studied cholinergic synapse, but the mechanisms by which acetylcholine is matched with acetylcholine receptors are not fully understood. Because alterations in neuronal calcium spike activity alter transmitter specification in embryonic spinal neurons, we hypothesized that receptor expression in postsynaptic cells follows changes in transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
112
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 52 publications
6
112
1
Order By: Relevance
“…Western blots were performed as previously described (20,49). Fractionation of cytosolic and nuclear protein fractions was done with NE-PER nuclear and cytoplasmic extraction reagents (Thermo Scientific) and samples processed according to manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blots were performed as previously described (20,49). Fractionation of cytosolic and nuclear protein fractions was done with NE-PER nuclear and cytoplasmic extraction reagents (Thermo Scientific) and samples processed according to manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo drug delivery was performed as previously described (20,21,49). Agarose beads (80 μm; BioRad) were loaded for at least 1 h with the indicated agents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertebrate skeletal muscle expresses five classes of neurotransmitter receptors at early developmental stages, four of which are eliminated during the achievement of the mature cholinergic phenotype. In this model, NMDA-and AMPAreceptor expression increases when activity is suppressed and decreases when activity is enhanced (3). Interestingly, under experimental glutamatergic innervation, the rat neuromuscular junction switches from cholinergic-to glutamatergic-type synapse (4).…”
mentioning
confidence: 99%
“…Because short-term plasticity often involves only one component of the synapse (22)(23)(24), the question arises: How does information about synaptic plasticity spread from its site of origin to recruit the other component of the synapse? Studies of synaptic growth during development have revealed a fairly elaborate program of pre-and postsynaptic changes involving a variety of orthograde and retrograde messengers (25), including activity-dependent or spontaneous release of the transmitter itself (26)(27)(28)(29)(30). We have now investigated the possible role of spontaneous transmitter release from the presynaptic neuron as an orthograde signal for recruiting the postsynaptic mechanisms of long-term plasticity.…”
mentioning
confidence: 99%